Toxicity of the Heavy Metal Lead (Pb) on the Development of Tilapia Fish Prolarvae (Oreochromis niloticus L.) - Harlis, Wa Ode; Malik, Nurhayu; Febrianto, Febrianto; Resman, Resman (Jurnal Pijar Mipa, 2025)
The heavy metal lead (Pb) entering the water has a negative impact on aquatic animals, one of which is tilapia (Oreochromis niloticus L.). The accumulation of lead (Pb) can disrupt the spawning process, cause morphological anomalies, and increase the mortality of tilapia sperm. This study was conducted to determine the toxicity of Lead (Pb) metal on the development of prolarvae of tilapia (Oreochromis niloticus L.). This research is a type of experimental research that is structured based on a Randomized Block Design (RBD) pattern, totalling 6 tilapia fish consisting of 3 male tilapia and 3 female tilapias. Tilapia eggs are obtained by injecting male and female broodstock using the hormone Ovaprim twice to stimulate gonadal maturity, after which fertilization is carried out, namely the merger between fish sperm cells and eggs in the container. After the eggs and sperm cells are fertilized, all eggs are divided into 5 treatments, and each treatment is filled with 20 eggs. The treatments consisted of control and 4 concentrations of Lead (Pb), namely 0.15 mg/L (P1), 0.30 mg/L (P2), 0.45 mg/L (P3), 0.50 mg/L (P4). Exposure to Lead (Pb) was given for 3 days, and observations were made after the eggs entered the prolarva stage to determine the degree of abnormality and various forms of abnormality. The observation parameter was the formation of abnormal types at the prolarvae stage. Data were analyzed using one-way ANOVA (Analysis of Variance) with a 95% confidence level and an LSD further test. The research results showed that the percentage of abnormalities in treatment P1 was 26.67%, P2 was 45%, P3 was 73.33%, and P4 was 83.33%. The abnormalities found were lordosis, kyphosis, scoliosis, yolk deformation accompanied by lordosis of the tail tip, and enlarged anterior yolk sac. Based on the results of the study, it is concluded that exposure to Lead (Pb) is toxic to tilapia larvae. It is hoped that the results of this research will provide input for the government and society regarding the importance of maintaining water quality from pollution